PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN IPS BERBASIS ANIMASI PADA KELAS VII SMP NEGERI 2 ANGKONA LUWU TIMUR - Ayu Setyawati, Nabilla; Arnidah, Arnidah; Valentino Sinaga, Andromeda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The use of Class VII Social Science learning media at SMP Negeri 2 Angkona, East Luwu Regency in its implementation has not been maximally used as a learning tool because it is only limited to the use of learning package source books / digital books from the Ministry of Education and Culture. These books are in the form of texts that tend to be informative, so that the teaching and learning process carried out in the classroom is still monotonous and still stuck with the lecture method which only gives students explanations about the material being taught. Based on this, this study aims to (1) describe the level of social studies learning video media needs based on animation; (2) design a valid animated learning video media; (3) determine the validity and practicality of social studies learning video media based on animation. This research uses an R&D (Research and Development) approach by adapting the interactive multimedia development and design model developed by Alessi and Trollip. This research was conducted at SMP Negeri 2 Angkona, East Luwu Regency. The subjects of this study were 25 students with details: 5 students for small group trials and 20 students for large group trials, and 1 subject teacher. Data collection used a small group trial questionnaire, a large group trial questionnaire and supporting documents in this study. The data analysis method consists of qualitative descriptive analysis and descriptive statistical analysis. The results showed that: (1) needs analysis is at the required level; (2) learning video media developed in the form of animation-based learning video media in Social Science subjects in Class VII; (3) product feasibility based on content/material validation with very valid results, media validation with very valid results; small group trials with practical results; large group trials with results in the very practical category, and subject teacher responses with results in the very practical category. The conclusion from the results of this study, the level of needs analysis of animation-based learning video media is in the needed category, the product in the form of MP4 video has been declared valid and practical.